Effect Of Online (Social) Media Influencers On Consumer Purchase Intent: A Young Generation Perspective - Patil , Swati; Wani , Nitin (Gyan Management Journal, 2024)
The growing use of online (social) media and mobile technologies made it easy for people to generate content and share details about their personal lives online. This has created an environment that has contributed to the rise of online (social) media influencers, a community of operators who attained a level of notoriety similar to that of celebrities in the online world. With the decreasing efficacy of conventional advertising strategies, more professionals have realised in recent years the importance of online (social) media influencers in promoting awareness of brand and sparking buyer dialogues (Lou et. al.,2021). In recent times, a increasing number of professionals acknowledged the significance of online (social) media influencers in augmenting brand recognition and adopting consumer dialogues, mainly considering their diminished efficacy of conventional marketing strategies (Baker 2021)